El ajuste secundario en materia de precios de transferencia, notas sobre su naturaleza y deficiente regulación en el Perú - Tartarini Tamburini, Tulio (2016)
This article addresses the subject of secondary adjustment on transfer pricing, focusing on its nature and its regulation in Peru. To do this, the author explains the concept and purpose of transfer pricing and also elaborates some terminological precisions concerning adjustments on transfer pricing, defining the primary adjustments, the compensating ones, the correlative ones and, in more depth, the secondary ones. Likewise, the author explains the way secondary adjustments of transfer prices are regulated by the Peruvian Income Tax Law.